5​(xminus​6)plus4equals7xminus4

1 answer

To solve the equation \( 5(x - 6) + 4 = 7x - 4 \), follow these steps:

  1. Distribute \( 5 \) on the left side: \[ 5x - 30 + 4 = 7x - 4 \]

  2. Combine like terms on the left side: \[ 5x - 26 = 7x - 4 \]

  3. Next, isolate \( x \) by moving \( 5x \) to the right side and \( -4 \) to the left side: \[ -26 + 4 = 7x - 5x \] \[ -22 = 2x \]

  4. Now, divide both sides by \( 2 \) to solve for \( x \): \[ x = -11 \]

So, the solution to the equation is: \[ \boxed{-11} \]